Introducing human rights: an overview including issues of gender justice, environment, and consumer law - South Asia Human Rights Documentation Centre (New Delhi, 2006)
This introductory text published by OUP India covers various aspects of international human rights law with a specific focus on the human rights movement in India, the Indian constitution and the role of the UN system. Addresses various related areas such as gender justice and human rights, as well as environmental law, and consumer law. It includes a glossary and suggestions for further reading.
Keywords: Human rights